Teachers’ Emoluments and Teachers Performance in Selected Secondary Schools in Iki-Iki Town Council in Budaka District - Nawire Fatina (Uganda Christian University, 2024)
The studyfocused on the relationship between teachers’ emoluments and teachers’ performance in selected secondary schools Iki-Iki town council in Budaka district. The specific objectives that guided the study included; to determine the relationship between teachers’ emoluments and teachers’ preparation of pedagogical documents, teachers’ classroom instruction and management and teachers’ assessment and evaluation of learners. The study basically used cross sectional survey which involved quantitative and qualitative designs. The study population was 99, which considered 95 teachers, 03 head teachers and 01 education officer while the sample size was 80.The data was analyzed using descriptive statistics; frequencies and percentages.